The role of regional capitals in the socio-economic development of regions. (3rd October 2022) - Khusnutdinova, Svetlana R.; Khusnutdinov, Rustem R.
The study reveals the role of regional capitals in the socio-economic development of their regions. The dynamics of the main demographic indicators (population, share of the population of capitals in the regional population, and natural population growth), socio-economic indicators (share of people older and younger than the working age, retail turnover, etc.) are analysed. The regions of the Volga Federal District, which capitals have a population above one million people are taken as a study site. The proportion of the population living in the studied capitals increases in relation to the population of the region. As a rule, the capitals take first place by average nominal salary in region. The Republic of Tatarstan is an exception. Regional capitals provide more than half of the regional retail turnover.